Sayam: Implementing Customary Law in The Resolution of Persecution Criminal Cases in Aceh - Roslaili, Yuni; Maulana, Muhammad; Maghfirah, Dinni; Suparwany, Suparwany (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2024)
Customary law has been used to decide certain criminal matters in Aceh instead of positive law. This was the case in the persecution incidents that occurred in various villages in the Meureudu region, where the idea of Sayam was employed. This study aimed to determine the practice of compensation in the concept of Sayam, the effectiveness of its use in resolving persecution and criminal conflicts, and whether there were any gaps between the concept of mediation in Indonesia and the concept of Sayam mediation in Aceh. This research used descriptive normative analysis and referred to legal pluralism, which considers the interplay of state, customary, and religious law using an empirical social approach. The results of this study found two types of procedures for reporting cases of persecution in the concept of Sayam: First, the complaint of the case was addressed to the village apparatus, and second, the complaint of the case was submitted to the police station. The technical compensation to the victim used four methods: deliberation, customary reusam, and losses, which were borne together based on the motto "saboh pisang koh dua" (one banana divided for two), and the last, based on the policy of traditional leaders. The gap between the concept of sayam in Aceh and the concept of mediation in Indonesia was that in the concept of sayam, as in general customary law, there was no recording, and in the concept of sayam, decisions were sometimes based on the decisions of traditional leaders.